Breastfeeding practices, appetite regulation and growth in healthy children in preschool - Soares, Daniela (2014)
Background Breastfeeding shapes food intake in children, through previous experience of basic flavors derived from the maternal diet by intrauterine life, by breast milk and also by the experience during the first year of life (Vereijken et al. 2011). In food choices, children only consider their preferences, based on known basic flavors, and these same preferences are now involved in appetite regulation (Faith et al. 2004). Developing the necessary skills to make safe and nutritious choices is undoubtedly a fundamental achievement that supports healthy growth. (Vereijken et al., 2011). Objective Evaluate the association between breastfeeding practices, the Appetite Regulation and Healthy Growth in children between 3 and 5 years old. Methodology A total of 327 children aged between 3 and 5 years old, living in the city of Braganza-Portugal and who attend kindergartens, were included in the sample. Two questionnaire were filled by parents of children: (1) A questionnaire regarding the regulation of appetite, Child Eating Behaviour Questionnaire-CEBQ (Wardle et al. 2001). adapted to Portugal (Viana et al. 2008), which includes eight scales: Food responsiveness—FR, Emotional over-eating—EOE, Enjoyment of food–EF, Desire to drink—DD, Satiety responsiveness—SR, Slowness in eating—SE, Emotional under-eating—EUE, Food fussiness— FF. (2) A Question about breastfeeding practices in the period of 0–6 months to identify if the child was exclusively breastfed or not. Finally we proceeded the anthropometric measurements (weight, height and calculate BMI) of children and them BMI were categorized according to CDC recommendations (Kuczmarski RJ et al. 2002). Statistical analysis was performed using the SPSS version 20.0 using the Kruskal–Wallis test (F) and Mann–Whitney-Wilcoxon test (Z). Results The sample mean age was 4 ± 0.8 years old. Children were mostly girls (51.7 %) and having been breastfed minority (43.7 %). A relation was found between breastfeeding practices and the score of one of from CEBQ scales (DD): FR(F = -0.185, p = 0.912), EOE(F = 2.436, p = 0.296), RS(F = 1.437, p = 0.488), SE(F = -0.463, p = 0.793), DD(F = 9.895, p = 0.007), SR(F = 1.877, p = 0.391), EUE(F = 1.428, p = 0.490), FF(F = 5.422, p = 0.066). A relation was found between the score of the scales of CEBQ and percentiles: FR(F = 7,435, p = 0.024), EOE(F = 4,757, p = 0.093), RS(F = 1,473, p = 0.479), SE(F = 4620, p = 0.099), DD(F = 1255, p = 0.534), SR(F = 0337, p = 0.845) EUE(F = 2566, p = 0.277), FF(F = 3038, p = 0.219). Conclusion We detected significant differences between breastfeeding practices and regulation of appetite, particularly in the desire to drink, suggesting that exclusively breastfed infants have a lower desire to drink when compared with the others. There is also the existence of a relation between relative-age percentile BMI and appetite regulation, namely the pleasure of eating. Thus, children who are overweight or obese have a greater pleasure in eating.